SSEP amplitudes add information for prognostication in postanoxic coma. (June 2021) - van Soest, Thijs M.; van Rootselaar, Anne-Fleur; Admiraal, Marjolein M.; Potters, Wouter V.; Koelman, Johannes H.M.T.; Horn, Janneke
Abstract: Objective: To investigate whether somatosensory evoked potential (SSEP) amplitude adds information for prediction of poor outcome in postanoxic coma. Methods: In this retrospective cohort study we included adult patients admitted after cardiac arrest between January 2010 and June 2018 who remained in coma and had SSEP recorded for prognostication. Outcome was dichotomized in poor (Cerebral Performance Category (CPC) 4–5) and good (CPC 1–3) at ICU discharge. Sensitivity of bilaterally absent N20 potential was calculated. In case the N20 potential was not bilaterally absent, the amplitude contralateral to stimulation side (baseline-N20, N20-P25, and maximum) was determined. At a specificity of 100%, SEPP amplitude sensitivities were determined for poor outcome. Results: SSEP recordings were performed in 197 patients of whom 57 had bilaterally absent N20 potentials. From 140 patients, 16 (11%) had a good outcome. The sensitivity for poor outcome of bilaterally absent N20 was 31%. At a specificity of 100%, contralateral amplitude thresholds were 0.34 μV (baseline-N20), 0.99 μV (N20-P25) and 1.0 μV (maximum), corresponding to a sensitivity for poor outcome of 38%, 44% and 40%. Combination of bilaterally absent N20 and a N20-P25 threshold below 0.99 μV yielded a sensitivity of 62%. Conclusions: Our results confirm that very low cortical SSEP amplitudes are highly predictive of poor outcome in patients with postanoxic coma. Adding 'N20-P25 threshold amplitude' to the 'bilaterally absent N20′ criterion, increased sensitivity substantially.